Penerapan Sistem Akuntansi Dasar pada Usaha Mikro, Kecil dan Menengah di Kecamatan Ngawi Kota - Muhammad Andi Hakim; Muslimin Muslimin (IPM2KPE, 2023)
This study aims to determine the understanding and application of the basic accounting system to MSMEs in Ngawi Kota District. The research method used is by using a qualitative method with a descriptive approach so that the researchers certainly go directly to the field to conduct observations, interviews, documentation. The results of the study show that many MSME actors in the Ngawi Kota District understand and apply the basic accounting system that have not yet implemented the basic accounting system. In conclusion, even though many MSME actors have not implemented the basic accounting system, there are also some who have implemented it so that the most important thing in a running business is still implementing it. Keywords: UMKM, Accounting System, Application of Accounting, Understanding